A Placental Sub-Proteome: The Apical Plasma Membrane of the Syncytiotrophoblast - Vandré, Dale D. (2012)
As a highly vascularized tissue, the placenta mediates gas and solute exchange between maternal and fetal circulations. In the human placenta, the interface with maternal blood is a unique epithelial structure known as the syncytiotrophoblast. Previously we developed a colloidal-silica based method to generate highly enriched preparations of the apical plasma membrane of the syncytiotrophoblast. Using similar preparations, a proteomics assessment of this important sub-proteome has identified 340 proteins as part of this apical membrane fraction. The expression of 38 of these proteins was previously unknown in the human placental syncytiotrophoblast. Together with previous studies, the current proteomic database expands our knowledge of the proteome of the syncytiotrophoblast apical plasma membrane from normal placentas to include more than 500 proteins. This database is a valuable resource for future comparisons to diseased placentas. Additionally, this dataset provides a basis for further experimental studies of placenta and trophoblast function.